Metschnikowia pulcherrima as biocontrol agent and wine aroma enhancer in combination with a native Saccharomycescerevisiae. (1st May 2023) - Canonico, Laura; Agarbati, Alice; Galli, Edoardo; Comitini, Francesca; Ciani, Maurizio
Abstract: One of the main objectives for a sustainable winemaking process is the reduction of the use of sulfur dioxide. In this regard, non- Saccharomyces wine yeasts are proposed as biocontrol agent in different steps of wine production chain. Here, a selected strain of Metschnikowia pulcherrima (DiSVA 269) and a native Saccharomyces cerevisiae low sulfite producer strain (DiSVA 708) were investigated. After preliminary laboratory trials, winemaking process at industrial level showed an effective biocontrol action (reduction of c.a. 1 Log order of wild yeasts) of M. pulcherrima inoculated at prefermentative stage in cold clarification (48 h at 10 °C) and during the subsequent fermentation process. The combination of M. pulcherrima/S. cerevisiae led a distinctive aromatic profile of wines both in laboratory and winery trials with a significant enhancement of ethyl butyrate, ethyl hexanoate, isoamyl acetate and β-phenyl ethanol. Moreover the use of the two selected strains was the best combination to enhance volatile thiols (3-mercaptohexan-1-ol and 3-mercaptoexil acetate) that well correlate with the sensory analysis (tropical fruits). The overall results indicate that the combined use of M. pulcherrima DiSVA 269 and native S. cerevisiae DiSVA 708 led a biocontrol action and an improvement of aromatic and sensorial profile of wine with low SO2 content. Highlights: Metschnikowia pulcherrima as bio-protectant at prefermentative stage. Metschnikowia pulcherrima improves aroma profile of wine. Fermentation trials conducted in winery conditions. Achievement of wines with low sulphites and desired aroma profile.